2014
DOI: 10.1158/0008-5472.can-13-1283
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Cytosolic Calcium Induces Necroptotic Cell Death in Human Neuroblastoma

Abstract: Necrosis has been studied extensively since the early days of medicine, with some patterns of necrosis found to be programmed like apoptotic cell death. However, mechanisms of programmed necrosis (necroptosis) are yet to be fully elucidated. In this study, we investigated how the hemagglutinating virus of Japan-envelope (HVJ-E) induces necrosis in mouse xenografts of human neuroblastoma cells. HVJ-E-induced necrosis in this system was found to depend on phosphorylation of the death receptor kinase receptor int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 38 publications
4
58
0
Order By: Relevance
“…Sustained increased cytosolic Ca ++ , upon reaching the soma, can modulate transcriptional programs, which, incidentally, may not all be pro-degenerative (Cho et al, 2013). Nonetheless, increased intracellular Ca ++ has been linked to the activation of necroptosis (Nomura et al, 2014), a form of programmed necrosis that has been shown to drive the death of motor neurons in animal models of both mutant SOD1 and sporadic ALS (Re et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Sustained increased cytosolic Ca ++ , upon reaching the soma, can modulate transcriptional programs, which, incidentally, may not all be pro-degenerative (Cho et al, 2013). Nonetheless, increased intracellular Ca ++ has been linked to the activation of necroptosis (Nomura et al, 2014), a form of programmed necrosis that has been shown to drive the death of motor neurons in animal models of both mutant SOD1 and sporadic ALS (Re et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HVJ-E-mediated cell death is induced by the recognition of HVJ-E RNA genome fragments with RNA receptor retinoic-acid inducible gene-I (RIG-I) or an elevation of the cytosolic Ca 2+ concentration [26, 34]. We found that HVJ-E failed to induce RIG-I expression in MM cells (NCI-H929, U266 and MM1S; Supplementary Figure 4A).…”
Section: Resultsmentioning
confidence: 74%
“…A recent report revealed that HVJ-E-induced cell death in human neuroblastoma cells depends on necrosis rather than apoptosis [19]. However, our previous studies showed that HVJ-E-induced apoptosis depends on caspase-8 activation in PC3 human prostate cancer cells and caspase-9 activation in murine B16F10 melanoma cells [6,7].…”
Section: Discussionmentioning
confidence: 81%